Vaping Synthetic Cannabinoids: A Novel Preclinical Model of E-Cigarette Use in Mice - Timothy W Lefever; Julie A Marusich; Brian F Thomas; Daniel G Barrus; Nicholas C Peiper; Richard C Kevin; Jenny L Wiley (SAGE Publishing, 2017)
Smoking is the most common route of administration for cannabis; however, vaping cannabis extracts and synthetic cannabinoids ("fake marijuana") in electronic cigarette devices has become increasingly popular. Yet, most animal models used to investigate biological mechanisms underlying cannabis use employ injection as the route of administration. This study evaluated a novel e-cigarette device that delivers aerosolized cannabinoids to mice. The effects of aerosolized and injected synthetic cannabinoids (CP 55,940, AB-CHMINACA, XLR-11, and JWH-018) in mice were compared in a battery of bioassays in which psychoactive cannabinoids produce characteristic effects. The most potent cannabinoids (CP 55,940 and AB-CHMINACA) produced the full cannabinoid profile (ie, hypothermia, hypolocomotion, and analgesia), regardless of the route of administration. In contrast, aerosolized JWH-018 and XLR-11 did not produce the full profile of cannabimimetic effects. Results of time course analysis for hypothermia showed that aerosol exposure to CP 55,940 and AB-CHMINACA produced faster onset of effects and shorter duration of action than injection. The ability to administer cannabinoids to rodents using the most common route of administration among humans provides a method for collecting preclinical data with enhanced translational relevance.